AN INTRODUCTORY OF PRODUCT INNOVATION AND MARKETING STRATEGY INTO SHELL WASTE-BASED SOUVENIR CRAFTS INDUSTRY IN THE CITY OF TANJUNG BALAI - Nurhayani, Ulfa; Azis, Adek Cerah Kurnia; Nasution, Akmal Huda; Herliani, Rini; Purba, Erni Luxy (Journal of Community Research and Service, 2018)
AbstractThe condition of the many shellfish wastes in Tanjung Balai City in North Sumatra Province makes a concern to the "Karya Working Group" as a part of Prosperous Family Income Improvement Business Group (an initiative from Indonesia™s National Family Planning board to improve family welfares; abbreviated as UPPKS) led by Mrs. Khalijah. The productivity of the Karya working group can be optimized considering that there are quite a lot of orders that have not been able to be fulfilled by them. Some of the obstacles in the management of this seashell handicraft business include the manual rinsing of seashells resulting in a long waiting time for further processing of production with the use of the same workforce; order-based marketing and relatively limited product innovation. In some aspects, similar shell craft products produced by competitors, especially in Java, have relatively better quality considering the products in question have been produced to scale exports to foreign countries. This mentoring activity in the management of product business managed by UPPKS Karya consisted of the use of technology for clamshell cleaning, assistance in utilizing e-marketing through social media and a more varied range of products that have contributed to increased effectiveness and efficiency in the production and marketing of handicraft products from clamshell waste produced by the Work UPPKS. In the future, UPPKS Karya's technological literacy is expected to continue to be able to increase its creativity through the exploration of product designs inspired by cyberspace for improving the competitiveness of products produced.Keywords: Shell Waste, Souvenir Crafts, E-Marketing, Tanjung Balai.